Interview with Antonio Candido - Heloisa Pontes (Revista Brasileira de Ciências Sociais, 2001)
Given in August 1987 and reviewed by the author in July 2001, this interview deals with important dimensions of Antonio Candido?s intellectual trajectory. By tracing the impact of the 1930 revolution within Brazilian culture and the decisive role of the foundation of Faculdade de Filosofia (Philosophy Department) of University of São Paulo for the im-plementation of a new pattern of intellectual work, Antonio Candido sets up the necessary context in order to understand cultural and political challenges pursued by him and others of his generation, such as Florestan Fernandes and many other members of Grupo Clima. The result is a vivid and thrilling image of the culture that permeated the process of institutionalization of Social Sciences in São Paulo